The Naples Score: Can it Outperform Existing Scores in Predicting Gastric Cancer Mortality? - Bahadır Kartal; Mehmet Berksun Tutan; Fatih Şahin; Ertugrul Gazi Alkurt (Hitit Medical Journal)

(untitled)
Objective: Gastric cancer surgery, including curative and palliative procedures, is crucial for managing gastric cancer. Accurate assessment of nutritional status is essential for risk stratification and improving patient outcomes. This retrospective study aims to identify the most reliable predictors of postoperative mortality by investigating the correlation between four nutritional scores and the mortality rate following gastric cancer surgery. Material and Method: This retrospective study evaluated 50 patients diagnosed with gastric adenocarcinoma and operated on at Hitit University Department of General Surgery between April 2021 and September 2023. Nutritional scores were calculated using albumin, cholesterol, neutrophil-to-lymphocyte ratio, and lymphocyte-to-monocyte ratio, along with mortality rates. Data collected included age, gender, operation type, laparoscopy usage, albumin, cholesterol, neutrophil-to-lymphocyte ratio, lymphocyte-to-monocyte ratio, mortality rates, and TNM stages. Nutritional scores were calculated, and their predictive accuracy for mortality was assessed using time-dependent Receiver Operating Characteristic curve analysis. Results: Significant differences in albumin levels, neutrophil-to-lymphocyte ratio, lymphocyte-to-monocyte ratio, and nutritional scores were found between deceased and surviving patients. Specifically, albumin levels were significantly lower in deceased patients (median = 3.5 mg/dL) compared to surviving patients (median = 4.1 mg/ dL, p=0.001). The median neutrophil-to-lymphocyte ratio was higher in deceased patients (p=0.005), and the median lymphocyte-to-monocyte ratio was lower in deceased patients (p=0.009). Among the scores, the Naples Prognostic Score was significantly associated with mortality but was outperformed by the Prognostic Nutritional Index. The Prognostic Nutritional Index had the highest predictive accuracy with an Area Under the curve of 0.792, a sensitivity of 76%, and a specificity of 86.2%, outperforming the others. Conclusion: Among the evaluated scores, the Prognostic Nutritional Index is the most effective predictor of prognosis. Its superior predictive accuracy suggests that the PNI can be utilized to enhance risk assessment and guide nutritional interventions in gastric cancer patients undergoing surgery.